Adsorption of carbon dioxide on Al/Fe oxyhydroxide - Pierre-Louis, Andro-Marc; Hausner, Douglas B.; Bhandari, Narayan; Li, Wei; Kim, Jongsik; Kubicki, James D.; Strongin, Daniel (Journal of colloid and interface science, 2013)
[Display omitted] ► The structure and reactivity of binary (Al/Fe) oxyhydroxide materials toward CO2 were elucidated. ► Infrared spectroscopy and and DFT computations were used to understand the binding of (bi)carbonate. ► At low mol% level (⩽20mol%), Al incorporated into the FeOOH without the formation of discrete AlOOH phases. ► The maximum amount of CO2 that adsorbs on the Al/Fe oxyhydroxide particle is at 30mol% Al. ► CO2 adsorption on Al/Fe oxyhydroxide forms bicarbonate bound on three distinct binding sites. The structure and reactivity of 0–70mol% Al/Fe iron oxyhydroxides (ferrihydrite in the absence and presence of Al) toward gaseous CO2 were investigated with X-ray photoelectron spectroscopy (XPS), atomic absorption (AA), scanning transmission electron microscopy with electron dispersive X-ray spectroscopy (STEM/EDS), X-ray diffraction (XRD), and attenuated total reflectance Fourier transform Infrared spectroscopy (ATR-FTIR) combined with density functional theory (DFT) calculations. Results showed that Al/Fe oxyhydroxide particles containing more than 20mol% Al consisted at least in part of Fe-oxyhydroxide with incorporated Al and a discrete AlOOH phase. Results from ATR-FTIR experiments and DFT calculations suggested that the bicarbonate complex formed by passing CO2 over the particles was accommodated on at least three distinct binding sites. At the lowest Al concentrations bicarbonate was bound to individual sites with primarily Fe or Al character. At the highest concentrations of Al (>20mol%) bicarbonate bound to discrete AlOOH phases became apparent. Results also suggested that the amount of CO2 adsorption for a given particle mass increased as the Al concentration was increased from 0 to 30%. This increase was likely due in large part to differences in the morphology of the particle aggregates that formed in the dry state, which would be expected to affect the amount of surface that was available to adsorb CO2.